2018
DOI: 10.15446/dyna.v85n207.71892
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of I-shaped steel beams with longitudinal stiffeners under lateral-torsional buckling

Abstract: This study focused on the experimental assessment of the behavior of I-shaped steel beams with longitudinal stiffeners under the action of lateral-torsional buckling. Thirty-three IPE-140 steel beams with and without longitudinal stiffeners were tested under simple-support conditions with a laterally unbraced length ranging from 0.69 to 6.0 m. The stiffeners spacing was 0.42 m, which represented three times the depth of the section. The structural behavior of the beams is discussed in terms of their flexural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In order to validate the experimental results of this research carried out at 1:9 scale, the measured moment vs laterally unbraced length Lb of the specimens without longitudinal stiffeners and with a ratio e/d = 3 were normalized and compared with the experimental results performed on a real scale in the work carried out by (Prado et al, 2018) as shown in Figure 8. Figure 8 shows a good concordance of the values of measured moment of the specimens tested at real scale and 1:9 scale in the inelastic and elastic buckling zone, validating the experimental results of this research, whereas in the plastic buckling zone, the measured moment values are associated to the material strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to validate the experimental results of this research carried out at 1:9 scale, the measured moment vs laterally unbraced length Lb of the specimens without longitudinal stiffeners and with a ratio e/d = 3 were normalized and compared with the experimental results performed on a real scale in the work carried out by (Prado et al, 2018) as shown in Figure 8. Figure 8 shows a good concordance of the values of measured moment of the specimens tested at real scale and 1:9 scale in the inelastic and elastic buckling zone, validating the experimental results of this research, whereas in the plastic buckling zone, the measured moment values are associated to the material strength.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Prado et al (2018) experimentally evaluated the use of longitudinal stiffeners with different laterally unbraced lengths Lb. The tests in this study were performed using only a spacing of 420 mm between longitudinal stiffeners, which represented an e/d ratio of 3, defined as the center-to-center spacing of the stiffeners divided by the depth of the section.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental study of four-point bending of beams IPE 140 equipped with longitudinal stiffeners at beam ends shows that such stiffeners are very effective especially for more slender beams [4].…”
Section: Introductionmentioning
confidence: 99%